1995
DOI: 10.1149/1.2050028
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study on the Selective Etching of Al0.25Ga0.75As Versus GaAs in Acidic Iodine Solutions

Abstract: To get insight into the selective etching of Al0.25Ga0.75normalAs with respect to normalGaAs in acidic I2+I− containing solutions, etch rate measurements on the (100)‐face of both materials were performed as a function of several variables. By combining these results with those of electrochemical measurements (including rotating disk electrode (RDE) and rotating ring‐disk electrode (RRDE) techniques), it was established that at Al0.25Ga0.75normalAs an electroless etching mechanism operates, whereas at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Instead the quantum efficiency for reduction of the oxidizing agent decreases from 2 to 1, before water begins to be reduced. 18 The reduction of IO 3in alkaline 18 and acidic 25 solutions is, in this respect, even more striking. At low light intensity a quantum efficiency close to 6 is observed, which drops to 1 as the photon flux is increased.…”
Section: Discussionmentioning
confidence: 84%
“…Instead the quantum efficiency for reduction of the oxidizing agent decreases from 2 to 1, before water begins to be reduced. 18 The reduction of IO 3in alkaline 18 and acidic 25 solutions is, in this respect, even more striking. At low light intensity a quantum efficiency close to 6 is observed, which drops to 1 as the photon flux is increased.…”
Section: Discussionmentioning
confidence: 84%
“…This strategy has been successfully applied previously to study the etching behavior of binary III-V semiconductors 10 and of the ternary materials Al 0.25 Ga 0.75 As and In 0.53 Ga 0.47 As. 11,12 In Ref. 11, it was demonstrated that the observed etching selectivity of Al 0.25 Ga 0.75 As vs. GaAs in acidic (I 2 ϩ I Ϫ )-containing solutions is essentially due to a difference in etching mechanism.…”
mentioning
confidence: 99%
“…This can be explained as follows. The diffusion limit of the etch rate ra is given by an expression of the type = kdc [13] with c the concentration of the etching reactant in solution and lc a proportionality constant which only depends on solution properties. For the rate of the actual surface reaction r,, an expression r, = k,c" [14] is assumed, with k, the rate constant and with 0 c a c 1.…”
mentioning
confidence: 99%